1993
DOI: 10.1111/1467-9566.ep11343802
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of stigma: the parents of autistic children

Abstract: This paper reports the findings of a qualitative study of courtesy stigma among 32 parents of autistic children. The results indicate that autism has uniquely stigmatising aspects because of the extremely disruptive nature of autistic symptoms, the normal physical appearance of autistic children, and the lack of public knowledge and understanding regarding the nature of autism. Most parents perceived themselves to be stigmatised by their child's disorder. There was a strong tendency for mothers to feel more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
219
1
26

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(267 citation statements)
references
References 13 publications
21
219
1
26
Order By: Relevance
“…ND youth can be stigmatized by broader society [12]. That stigmatization extends into online gaming communities where ND children may encounter situations where they are discussed in subtle and notsubtle ways.…”
Section: Minecraft and Neurodiverse Playersmentioning
confidence: 99%
“…ND youth can be stigmatized by broader society [12]. That stigmatization extends into online gaming communities where ND children may encounter situations where they are discussed in subtle and notsubtle ways.…”
Section: Minecraft and Neurodiverse Playersmentioning
confidence: 99%
“…Studies of those who are bereaved by suicide have found a sense of stigmatisation to be common (Dunn andMorrish-Vidners 1987, Wertheimer 2001). While individuals will experience courtesy stigma in different ways (Gray 1993), it seems reasonable to assume that the stigma of suicide will pose particular difficulties for parents whose children take their own lives while young. Harden (2005) has drawn attention to the understanding of parenting that characterises late modernity, in which the creation of a happy, healthy, well-socialised child constitutes a major project.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that parents during this era were isolated, with few resources or information to help them. When parents were believed to have caused their child's autism they were scrutinised, treated, researched and stigmatised by both professionals and the public (Fraknoi & Ruttenberg, 1971;Gray, 1993).…”
Section: Social Awareness and Service Provisionmentioning
confidence: 99%
“…This may affect social workers' and other professionals' abilities to provide access to social care support for older carers and people with autism themselves. Inadequate social supports for parents, poor societal awareness and limited understanding of autism are considered among the most stressful aspects of parenting a child with autism (Gray, 1993;Sharpley, Bitsika, & Efremidis, 1997). Through practical, informational and emotional support and effective social care and social work support these stresses may abate; this is a dominant motif of current policy for carers of individuals with autism.…”
Section: Social Carementioning
confidence: 99%